Los límites de la humanidad. El mito de los ch’ullpa en Marcapata (Quispicanchi), Perú - Pablo F. Sendón (Journal de la Société des Américanistes)
The limits of humanity. The myth of the ch’ullpa in Marcapata (Quispicanchi), Peru. This paper presents and discusses the myth of the ch’ullpa – beings of the pre-solar time – such as it is narrated by the members of the ayllu Collana from the district of Marcapata (province of Quispicanchi, Cusco) in relation to three kind of sources: a) the archaeological information about the geographical and spatial localization of the mortuary monuments which received that name in the Central Andes; b) the ethnological information about other versions of the myth registered among other indigenous-peasant populations from Southern Peru and the Bolivian altiplano; c) the ethnohistorical information which, in relation with the myth, has been registered by several scholars. The main objective of the review is to lay the foundations of a comparative perspective of the myth with the aim to transcend the specificities of a case study.